Posted by **rajan** on Friday, August 16, 2013 at 1:16pm.

prove that :cosA-sinA+1/cosA+sinA-1=cosecA+cotA

## Answer This Question

## Related Questions

- mathematics trignometry - prove that the following are identity 1. (cotA+cosecA-...
- Maths - Prove that [sinA/(1-cosA)-(1-cosA)/sinA]*[cosA/(1+sinA)+(1+sinA)/cosA]=...
- trig - Establish the following identity: CosA/1-TanA + SinA/1-CotA = CosA-SinA
- Maths - Hi, can someone give me the answer to this question: secA-tanA=1/4. Find...
- further mathematics - Let P=(cosA sinA) (sinA cosA) Q=(cosB sinA) (sinB cosA) ...
- trig - Prove : (sinA-cosA+1)/(sinA+cosA-1) = (1+sinA)/cosA
- trig - Please help me how to do this: 1) 1 + sina*cosa / (cosa + sina)^2 = 2) ...
- trigonometry - x×sin^3A=y , cos^3A = sinA × cosA , x×sinA= y×cosA , then prove ...
- maths(trigonometry) - prove that sinA-cosA+1/sinA+cosA-1=1/secA-tanA
- trig - I need to count this: a) 1-tg^2a/1+ctg^2a, when sina =2/3 b) 1-tg^2a/1-...

More Related Questions